Minimal Clinically Important Difference, Substantial Clinical Benefit, and Patient Acceptable Symptom State of Outcome Measures Relating to Shoulder Pathology and Surgery: a Systematic Review - Su, Favian (Curr Rev Musculoskelet Med, 2021)
PURPOSE OF THE REVIEW: To provide a comprehensive summary of available literature on the minimal clinically important difference (MCID), substantial clinical benefit (SCB), and patient acceptable symptom state (PASS) of patient-reported outcome measures (PROMs) for various shoulder conditions and outcomes and to identify factors that influence these metrics. RECENT FINDINGS: Over the past 2 years, there has been an increasing interest in utilizing MCID, SCB, and PASS as a gauge to evaluate the success of an intervention for shoulder conditions. Efforts at calculating these thresholds have yielded multiple and inconsistent values and are further compounded by the proliferation of different PROMs in the shoulder literature. SUMMARY: The MCID, SCB, and PASS values of shoulder PROMs vary widely with study-specific characteristics, including patient demographics, shoulder pathology, treatment, shoulder instrument, study methodology, and calculation method. The differences in these factors are not inconsequential and could lead to large discrepancies in threshold values. It is crucial that clinicians are mindful of these variables when designing future studies to calculate these metrics or when utilizing previously published values to determine the success of an intervention. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12178-020-09684-2.